Implementasi Peraturan Daerah Nomor 7 Tahun 2021 tentang Penanggulangan Anak Jalanan, Gelandangan dan Pengemis di Kota Pasuruan Jawa Timur - Aulia Nisya Salshabila; Radjikan Radjikan; Muhammad Roisul Basyar (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The phenomenon of street children, vagrants, and beggars is still a fairly complex social problem in Pasuruan City. The Pasuruan City Government has issued Regional Regulation Number 7 of 2021 as an effort to overcome the existence of street children, vagrants and beggars who are considered to disturb public order. This study aims to determine how the policy is implemented and identify supporting and inhibiting factors for its implementation. This study uses a qualitative research method with a descriptive approach and uses the Van Metter and Van Horn policy implementation theory as the basis for analysis. The results of the study show that although the policy has fairly clear standards and targets, its implementation has not been optimal due to the lack of resources, the unavailability of special rehabilitation facilities in Pasuruan City, and the weak ongoing commitment of the implementers. Coordination between implementing agencies is also not fully synergistic. Therefore, the successful implementation of this Regional Regulation requires improvements in aspects of resources, rehabilitation facilities, and strengthening cross-agency cooperation. A stronger commitment is needed from the local government so that handling street children, vagrants and beggars can be carried out more comprehensively and sustainably.